Analisis Substitusi Konsumsi Jagung sebagai Alternatif Karbohidrat terhadap Elastisitas Permintaan di Pasar Ciawitali - Icha Anisa Indriany; Hani Rohmat; Alfhan Firansa; Rahma Putri Suparman; Ira Murwenie (Asosiasi Riset Ilmu Manajemen dan Bisnis Indonesia, 2025)
This study aims to analyze corn consumption substitution as an alternative carbohydrate source and to measure the demand elasticity of corn in response to fluctuations in corn and rice prices at Ciawitali Market, Garut Regency. Primary data were collected through observations and interviews, along with secondary data from West Java Central Statistics Agency processed using simple linear regression and cross-elasticity analysis with SPSS. Results show that changes in corn prices explain 99.7% of variation in corn demand with a positive coefficient of 0.827, indicating a substitution effect with rice, which experienced a concurrent price increase. The cross-elasticity value of 1.64 confirms the elastic substitution relationship between corn and rice. These findings highlight the potential of corn as a substitute for rice in maintaining stable food consumption despite fluctuations in staple commodity prices.